Efektivitas Program One Gate, One Billing and One System dalam Pemberantasan Pungli di Pelabuhan - Hanafie, Haniah (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2023)
This research concerns the One Gate, One Billing and One System Program and extortion at the Port. The purpose of this study is to explain the effectiveness of the One Gate, One Billing and One System Program in preventing extortion at Tanjung Priok Port and the inhibiting factors for implementing the One Gate, One Billing and One System Program. A qualitative approach with descriptive data analysis techniques was used in this study. Program effectiveness theory as an analytical framework. Data was collected by interviews, document review and observation. The results of the study show that the One Gate, One Billing and One System Program is not effective in preventing extortion at Tanjung Priok Port. There are cultural factors, weak supervision, the economy and abuse of authority by officers, making eradication of extortion difficult to overcome.